Syringomyeli hos hund - Zanders, Sofie (2011)
The canine population has during it’s time with humans gone through at least 2 major genetic bottlenecks, the first when it was separated from the wolf, and the second when it was divided into different breeds. Among other things, this has lead to the accumulation of unwanted genes, such as genes causing disease in dogs. One such inherited disease is syringomyelia, which has proven to be more common than expected, especially in certain smaller breeds such as the Cavalier King Charles Spaniel. Syringomyelia in dogs is often a secondary condition caused by the malformation called occipital hypoplasia. Occipital hypoplasia means that the back part of the skull is too small to fit the cerebellum, and the cerebellum is therefore partially forced into the cavity known as the foramen magnum that connects the brain and the spinal cord. This disrupts the flow of spinal fluid, and fluid-filled cavities, syrinxes, develop within the spinal cord of the dog. These cavities are what define syringomyelia. The syrinxes cause many disturbing neurological symptoms, most predominantly pain. The treatments that exist today are largely based on the ones used on humans, and they have, at most, been moderately successful in dogs. The Cavalier breed clubs are today working hard to eliminate the disease from the breeding population, but the research into the genetic background of the disease has not yet reached its goal of identifying the causative mutations. The breeding recommendations that exist today are largely based on phenotypic observations on the individual dog, but also on the information that is known about the dogs relatives. Current research is now mainly focused on localizing candidate genes, so that a DNA test eventually can be developed to identify dogs that carry the genes for syringomyelia. This will later lay the foundation for the new breeding recommendations that will be set towards the goal of eliminating the disease from the breed. Today, the breeding guidelines are based solely on phenotypic observations, such as if the dog shows symptoms at a certain age.